Free Flap Reconstruction of Posterior Trunk Soft-Tissue Defects: Single-Institution Experience and Systematic Literature Review. Issue 3 (2nd October 2021) - Akdeniz-Dogan, Zeynep; Roubaud, Margaret S.; Kapur, Sahil K.; Liu, Jessie; Yu, Peirong; Selber, Jesse C.; Mericli, Alexander F.
Abstract : Background: The posterior trunk is a technically demanding location for microvascular free tissue transfer. In this study, the authors report their own institutional experience with soft-tissue free flap reconstruction of the posterior trunk and provide a systematic review of the literature regarding this uncommon clinical scenario. Methods: A systematic review was performed using the PubMed database in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. A single-institution retrospective review was also performed including all patients who received a soft-tissue free flap for a posterior trunk defect between 1990 and 2019. Results: The database search yielded 15 articles, representing 61 patients; the most commonly used flap was the latissimus dorsi (45.9 percent) and the most commonly reported defect location was the lumbosacrum (42.3 percent). Retrospective review of the authors' database identified 26 patients, with the latissimus dorsi being the most common flap and the sacrum the most common defect site. The authors' institutional case series showed a 30.7 percent major complication rate and 7.7 percent total flap loss rate; 38.4 percent of flaps required vein grafting. Conclusions: In this study, the authors provided a systematic literature review and described their own long-term institutional experience with these rare and difficult reconstructions. Although the overall complication rate is high, these reconstructions are frequently necessary, and an algorithmic approach can improve outcomes. CLINICAL QUESTION/LEVEL OF EVIDENCE: Therapeutic, IV.